The effect of the menstrual cycle on collagen metabolism, growth hormones and strength in young physically active women - Iwańska, Dagmara; Kęska, Anna; Dadura, Emilia; Wójcik, Agnieszka; Mastalerz, Andrzej; Urbanik, Czesław (Biology of Sport, 2021)
This study aimed to investigate the effect of the menstrual cycle on strength, functioning of the GH/IGF-1 axis and collagen metabolism in physically active women. Twenty-four physically active and eumenorrheic women volunteered to participate in the study (body mass 60.3 ± 9.18 kg, age 21.8 ± 0.92 years). Blood samples were obtained between the 5th and 8th days (the follicular phase) and between the 19th and 22th days (the luteal phase) of the menstrual cycle to determine sex steroid concentrations (follicle-stimulating hormone (FSH), luteinizing hormone (LH), prolactin (PRL), oestradiol (E2) and progesterone (P)). Also insulin-like growth factor 1 (IGF-1) and collagen metabolism markers (synthesis (PICP) and breakdown (ICTP)) and maximum voluntary contraction (MVC) were measured. MVC was higher in the luteal phase 164.1 ± 34.77 [N m] (F(1.23) = 4.59; p = 0.043). The recorded collagen synthesis marker (PICP = 296.4 ± 35.61 [ng/ml]) was at the upper level of the reference range (30–300), with an insignificant decrease in the luteal phase (Z = 1.612; p = 0.107) and a significant increase in oestradiol concentration (Z = 4.286; p = 0.0001). The marker of collagen breakdown (ICTP = 4.16 ± 0.68 [µg/l]) wasreduced by 6.8% in the same phase (Z = 1.764; p = 0.137). The variability of physical abilities (MVC) during the menstrual cycle showed that menstrual status should be taken into account in determination of the training loads. Increasing the load in the luteal phase seems to be favoured by a beneficial change in collagen metabolism (lower synthesis decrease, lower breakdown increase) observed in physically active women.